Implikasi Filosofis Asbabun Nuzul dalam Ilmu Al-Qur’an - Manggala, Kayan; Toriquddin, Moh.; Kharis Alwi , Mohamad; Syihabuddin , Muhammad; Hamzah , Hakma (CV Kalimasada Group, 2023)
The Al-Qur'an is the holy book of Muslims which is the first source of Islamic teachings that must be believed. In the process of its descent, it underwent many processes in which its decline occurred both because of the form of questions and the events that occurred. The Al-Qur'an was revealed to giving guidance to humans so that they can follow the path of truth by upholding the principles of life based on faith in Allah and also informing them of things that have passed, current events and those that will come. At first most of the Qur'an was revealed for general purposes but during the time of Rasulullah SAW and his companions they witnessed many historical events as well as special events as well as questions about law so that they required firmness and asked for detailed explanations about religious matters so several verses were revealed from Al-Qur'an to answer questions that arise, this is what is meant by Asbabun Nuzul... Researchers realize how important the Al-Qur'an is for Muslims, so the Al-Qur'an is not just for reading and understanding its meaning. but we also have to know the reasons why the verses in the Koran were revealed by Allah SWT. In research on Asbabun Nuzul in the Qur'an, we will discuss various things related to Asbabun Nuzul, including the meaning of Asbabun Nuzul, its types and divisions, rules, specifications and the benefits of studying Asbabun Nuzul as well as the philosophical implications of Asbabun Nuzul in Qur'anic sciences. 'an.